Analysis of the Illegal Landfills Ocurrence in La Palma Island, Spain. - Quesada-Ruiz, Lorenzo Carlos (Revista de Estudios Andaluces, 2017)
The proliferation of Illegal landfills (IL) has negative impacts on the environment and the economy, especially in both, ecological sensitive and touristic areas. This work focuses on the characterization of illegal landfills located in La Palma Island. 153 IL were obtained through field work and the visual interpretation of digital ortho-images at a spatial resolution 0.5 m for 2012 and 2015. This information was included within a geospatial database together with a set of 150 potential explanatory features of different typology: type of waste, surveillance and control, socioeconomics, accessibility, distance to elements of interest, visibility and terrain features. Multivariate analyses such as exploratory analysis (EA), factor analysis (FA) and discriminant analysis (DA) were applied to assess the degree of association between the explanatory features and the IL occurrence. AF explained a cumulative variance of 82.34% considering 7 factors (Kaiser-Meyer-Olkin test: 0.71). AD showed a canonical correlation of 0.78. AD leaded to discriminating between affected areas and non-affected areas using features such as: population density, slope, Normalized Difference Vegetation Index (NDVI) or distance to agricultural areas or distance to urban centers. Additionally, AF identified the former features as the main drivers of IV occurrence.